2005
DOI: 10.1161/01.res.0000187473.85419.3e
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Vascular Endothelial Cell Transient Receptor Potential Channels

Abstract: Abstract-Among the 28 identified and unique mammalian TRP (transient receptor potential) channel isoforms, at least 19 are expressed in vascular endothelial cells. These channels appear to participate in a diverse range of vascular functions, including control of vascular tone, regulation of vascular permeability, mechanosensing, secretion, angiogenesis, endothelial cell proliferation, and endothelial cell apoptosis and death. Malfunction of these channels may result in disorders of the human cardiovascular sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
231
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 240 publications
(237 citation statements)
references
References 112 publications
(185 reference statements)
4
231
1
1
Order By: Relevance
“…ECs contain a range of different TRP channels (21), and in resistance arteries, TRPV4 channels are intimately involved in vasodilation to EC-dependent agonists (22,23) and shear stress-induced dilation (24). Sustained activation to low pressure is a unique addition to this list.…”
Section: Discussionmentioning
confidence: 99%
“…ECs contain a range of different TRP channels (21), and in resistance arteries, TRPV4 channels are intimately involved in vasodilation to EC-dependent agonists (22,23) and shear stress-induced dilation (24). Sustained activation to low pressure is a unique addition to this list.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is worth noting that a number of different endothelial calcium-permeable channels are substrates for PKA phosphorylation, including some members of the transient receptor potential (TRP) superfamily of proteins. Interestingly, some of them (including TRPV1 and TRPV4) are also regulated by AA and its metabolites, as well as by NO through S-nitrosylation (23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…A partial depolarization of plasma membrane by receptor stimulation is reported to increase the frequency of Ca 2ϩ oscillations, leading to activation of nuclear factor of activated T cells (NFAT), a transcription factor that is predominantly regulated by calcineurin (10). Recent reports have indicated that transient receptor potential canonical (TRPC) subfamily proteins play an essential role in agonistinduced membrane depolarization (11,12). The relevance of TRPC channels to pathological hypertrophy is underscored by the observations that heart-targeted transgenic mice expressing TRPC channels caused hypertrophy (13,14) and that TRPC proteins were up-regulated in hypertrophied and failing hearts (14 -17).…”
mentioning
confidence: 99%